Posterior Spinal Osteotomies for Sagittal Imbalance. Issue 1 (April 2016) - El-Sharkawi, Mohammad; Tammam, Hamdy; El-Sherif, Essam; Adam, Faysal; Refae, Hesham
Introduction: Surgical treatment of spinal deformity offers superior clinical and radiographic outcomes than non operative approaches. This prospective study aimed at assessment of outcomes of posterior only spinal osteotomies in treatment of sagittal imbalance. Patients and Methods: Thirty cases of symptomatic sagittal imbalance were managed with posterior spinal osteotomy in Assiut University Hospitals. Half of them were males, age ranged from 5–57 years (20 ± 12.9). Eleven cases were congenital (36.7%) and five cases were Scheuermann kyphosis (16.7%), with other causes (46.7%) including degenerative, junctional, ankylosing spondylitis, post tuberculous, neuromuscular and Idiopathic types. Curves were angular in 14 cases (46.7%) and smooth in sixteen (53.3%). Ten cases (33%) were thoracic, eight (27%) were thoracolumbar, six (20%) were lumbar and six cases were diffuse. VAS, ODI, SRS-22, neurology, and radiological parameters (SVA, TK, LL T1SPA, PI, PT and SS using Surgimap 2.0.8.4664) were compared pre, post and at last follow up visit. Operative time, bleeding amount, and correction achieved were compared. The mean follow up was 21 months (12–60 months). Results: Seventy five osteotomies (59 Ponte Osteotomies "PO" in 19 cases, Six Pedicle Subtraction Osteotomies "PSO" in 4 cases and ten Posterior Vertebral Column Resections "PVCR" in10 cases) had been done. Thirty nine osteotomies (52%) were thoracic, 17 thoraco-lumbar and 19 were lumbar. The VAS, ODI and total SRS-22 were improved ( p = 0.001) with no difference between the three osteotomy types. The local kyphosis improved from 61° to 10.57° ( p = 0.001) with 82.7% final correction and no difference between PVCR and PO ( p = 0.017). TK improved from 43.86° to 30.47 ° ( p = 0.020). The mean SVA improved from 54.68 mm preoperatively to 33.48 mm postoperatively and was 35.16 mm at final follow up ( p = 0.023). The amount of blood loss and the mean operative time was less with PO than PSO and VCR ( p = 0.001 and p = 0.039). Two cases developed deep infection and were successfully managed with debridement and antibiotics. Four cases developed asymptomatic proximal junctional kyphosis. Two cases with postoperative neurological complications were encountered. One of them recovered spontaneously during the follow up. The other one had proximal junctional failure and atraumatic subluxation of the upper dorsal spine. Urgent reduction and proximal extension of the fixation and fusion was done. Complete neurological recovery was observed during the follow up. Conclusion: Posterior only spinal osteotomies appear to be highly effective in correcting sagittal imbalance and may avoid the morbidity of anterior or combined approaches.